Biological properties of Schinus terebinthifolia Raddi essential oil - Priscilla Guimarães Silva Vasconcelos; Érika Ponchet Alves; Carolina Medeiros de Almeida Maia; Arella Cristina Muniz Brito; Diego Romário Silva; Irlan Almeida Freires; Yuri Wanderley Cavalcanti; Vera Lucia Garcia Rehder; Ana Lúcia Tasca Gois Ruiz; Marta Cristina Teixeira Duarte; Pedro Luiz Rosalen; Gustavo Pina Godoy; et al. (Universidade de São Paulo, 2022)
Abstract Schinus terebinthifolia Raddi green fruits essential oil (EO) was evaluated regarding its phytochemical profile, antimicrobial and cytotoxic activities, and toxicity. Gas chromatography with mass spectrometry was applied to identify its constituents, thereafter the minimum inhibitory concentration, minimum bactericidal and fungicidal concentrations, and its antibiofilm activity were evaluated. The EO cytotoxicity was assessed in tumor and non-tumor human cells, and in vivo toxicity was evaluated in a Galleria mellonella model. The major constituents of S. terebinthifolia EO were alpha-phellandrene and beta-phellandrene. The EO had a weak activity against all strains of Candida albicans (MIC 1000μg/mL) and had no activity against non-albicans strains, bacteria, and C. albicans biofilm. Cytostatic activity against all tumor cell lines was shown. Additionally, cell viability remained at EO concentrations up to 62.5 μg/mL. At 16 mg/mL, 50% hemolysis was observed, and it had low toxicity in vivo. Overall, the S. terebinthifolia EO was characterized by low antimicrobial and antibiofilm activities, with no evidence of toxicity to human tumor and non-tumor cells.